2015
DOI: 10.1007/s00248-015-0653-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Variation Across Amphibian Skin Regions: Implications for Chytridiomycosis Mitigation Efforts

Abstract: Cutaneous bacteria may play an important role in the resistance of amphibians to the pathogenic fungus Batrachochytrium dendrobatidis (Bd). Microbial communities resident on hosts' skin show topographical diversity mapping to skin features, as demonstrated by studies of the human microbiome. We examined skin microbiomes of wild and captive fire-bellied toads (Bombina orientalis) for differences across their body surface. We found that bacterial communities differed between ventral and dorsal skin. Wild toads s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 56 publications
5
64
2
Order By: Relevance
“…In exotic species, most NGS studies have focused on characterizing the skin microbiota of amphibians . The most common phylotypes colonizing their skin include Bacteroidetes, Proteobacteria, Firmicutes and Sphingobacteria (Table ).…”
Section: The Skin Of Animals Are Inhabited By An Even More Diverse MImentioning
confidence: 99%
See 2 more Smart Citations
“…In exotic species, most NGS studies have focused on characterizing the skin microbiota of amphibians . The most common phylotypes colonizing their skin include Bacteroidetes, Proteobacteria, Firmicutes and Sphingobacteria (Table ).…”
Section: The Skin Of Animals Are Inhabited By An Even More Diverse MImentioning
confidence: 99%
“…One study found that different amphibian species were strong predictors of microbial community composition and wetland sites explained significant variations across the same species of amphibians . Furthermore, another study found wild toads had greater bacterial richness and diversity than captive toads …”
Section: The Skin Of Animals Are Inhabited By An Even More Diverse MImentioning
confidence: 99%
See 1 more Smart Citation
“…But captivity alters the microbiome in mammals (Uenishi et al, 2007; Delsuc et al, 2014; Kreisinger et al, 2014; Clayton et al, 2016; Delport et al, 2016), birds (Scupham et al, 2008; Matsui et al, 2010; Wienemann et al, 2011; Rodríguez-Ruano et al, 2015; Wang et al, 2016), fish (Dhanasiri et al, 2010), reptiles (Keenan et al, 2013), and amphibians (Loudon et al, 2013; Becker et al, 2014; Bataille et al, 2016), which is likely due to the dietary, social, and environmental conditions of captivity that are so different from those experienced in the wild. Captive microbiomes likely do not represent the natural variation of the microbiome of a species (or population), which is necessary for evolutionary analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the microbiome may also have an indirect influence on host health during interactions with infectious pathogens (Turnbaugh et al , ; Heijtz et al , ; Honda & Littman, ; Theis et al , ; Jani & Briggs, ). All amphibians show an important and diverse microbiota community on their permeable skin, which is thin and sensitive to their environment (Duellman & Trueb, ; Bataille et al , ). Amphibian species are mainly habitat specialists inhabiting specific ecological niches associated with water and humidity (Hernandez, ).…”
Section: Introductionmentioning
confidence: 99%